Serum BMP-2 and BMP-4 levels and their relationship with disease activity in patients with rheumatoid arthritis and ankylosing spondylitis - Ali Erhan Özdemirel,; Serdar Can Güven,; Zühre Sarı Sürmeli,; Ayla Özyuvalı,; Memet Kurt,; Diana Rüstemova,; Ayşe Peyman Yalçın Sayan,; Hüseyin Tutkan,; Şebnem Ataman, (Archives of Rheumatology, 2022)
Objectives: This study aims to investigate the levels of bone morphogenic proteins (BMPs), one of the pathways affecting bone turnover in these diseases, and to investigate their relationship with disease activity. Patients and methods: Between September 2013 and July 2015, a total of 100 ankylosing spondylitis (AS) patients (53 males, 48 females; median age: 40 years; range, 18 to 62 years), 58 rheumatoid arthritis (RA) patients (25 males, 33 females; median age: 40.5 years; range, 26 to 59 years), and 102 age- and sex-matched healthy controls (55 males, 47 females; median age: 38 years; range, 18 to 55 years) were included in the study. In all groups, serum BMP-2 and BMP-4 levels were measured using enzyme-linked immunosorbent assay (ELISA). Demographic data (age, sex, duration of disease) and acute phase reactants of the patients at the final visit were recorded. Disease activity was assessed through the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and Ankylosing Spondylitis Disease Activity Score C-Reactive Protein (ASDAS-CRP) for AS patients and through the Disease Activity Score-28-CRP (DAS-28-CRP) for RA patients. Results: The median BMP-2 values were found to be significantly higher in the RA group compared to the other groups and in the control group compared to the AS group (p<0.001 for both). There was no significant difference between the groups in terms of median BMP-4 values (p>0.05). No significant relationship was found between serum BMP-2 and BMP-4 levels and disease activity in both AS and RA patients, while there was a weak positive correlation between erythrocyte sedimentation rate and CRP levels with BMP-2 level in RA patients (p=0.014, r=0.320 and p=0.029, r=0.287, respectively). Conclusion: Our study results suggest that the BMP pathway may have different dual effects in AS and RA patients depending on the underlying pathogenesis, and that local effects are more prominent than serum levels.